Literature Review the Effect of Division of Work and Workload on Work Effectiveness and its Impact on Employee Performance - Nugroho Dwi S, Adi; Hapzi Ali (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Determination Work Effectiveness and Employee Performance: Analysis of the Division of Work and Workload , A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research . The results of this research library are that: 1) Division of Work has an effect on Work Effectiveness; 2) The division of labor has an effect on employee performance; 3) Workload affects Work Effectiveness; 4) Workload affects employee performance; and 5) Work Effectiveness has an effect on Employee Performance.